Customer Loyalty Behaviour Brand Air Conditioner XYZ: Combination of Expectation- Confirmation Theory, Satisfaction – Loyalty, and Brand Reputation - Dendy, Masyiakh K.; Satria, Fadil P.; Lin, Shu-Chiang (Institut Teknologi Sepuluh Nopember, 2020)
This research studies about AC (Air Conditioner) consumer loyalty in the city of Surabaya. The combination of Expectation Confirmation Theory theory on AC consumer satisfaction, the relationship between satisfaction and loyalty with the presence of brand reputation variables. The use of structure equation modeling methods can provide a clear picture of the relationship between variables. From the data processing can be seen if the relationship between satisfaction with loyalty variables significantly influence the value of 0.901 and the relationship of satisfaction variables with the brand reputation that has a significant effect with the value of 0.989. The expectation in this research is to be able to find out the factors that can influence the consumer loyalty of the XYZ brand AC so that it can be used as a reference in taking strategic steps of the company.